Selection of Nuclear Polyhedrosis Virus Resistant Crosses of Silkwork, Bombyx mori L. Through Line x Tester Analysis - Rahman, SM; Ali, IA; Alim, A (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Heterosis; combining ability; Bombyx mori; larval survival; NPV disease Bangladesh j. genet. biotechnol. 5 (1&2): 45-47, 2004 (June & December)